Heat transfer of viscoelastic fluid flow due to non-linear stretching sheet with internal heat source - Nandeppanavar, Mahantesh M.; Siddalingappa, M.N.; Jyoti, H. (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, a viscoelastic boundary layer flow and heat transfer over an exponentially stretching continuous sheet in the presence of a heat source/sink has been examined. Loss of energy due to viscous dissipation of the non-Newtonian fluid has been taken into account in this study. Approximate analytical local similar solutions of the highly non-linear momentum equation are obtained for velocity distribution by transforming the equation into Riccati-type and then solving this sequentially.
Keywords: viscoelastic fluid; boundary layer flow; exponential stretching sheet; heat source/sink; heat transfer; skin friction